2000
DOI: 10.1074/jbc.m003030200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Hyaluronan Receptor for Endocytosis (HARE)

Abstract: Rat liver sinusoidal endothelial cells (LECs) express two hyaluronan (HA) receptors, of 175 and 300 kDa, responsible for the endocytic clearance of HA. We have characterized eight monoclonal antibodies (mAbs) raised against the 175-kDa HA receptor partially purified from rat LECs. These mAbs also cross-react with the 300-kDa HA receptor. The 175-kDa HA receptor is a single protein, whereas the 300-kDa species contains three subunits, ␣, ␤, and ␥ at 260, 230, and 97 kDa, respectively (Zhou, B., Oka, J. A., and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
222
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(227 citation statements)
references
References 60 publications
5
222
0
Order By: Relevance
“…Another candidate is the HA receptor for endocytosis. It can be expressed on the cell surface, but it predominately localizes within sinusodial endothelia and its expression by lymphocytes has not been reported (35,36). Interestingly, antibody blockage of HA binding to HA receptor for endocytosis impairs tumor cell metastasis, a process likened to active lymphocyte extravasation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate is the HA receptor for endocytosis. It can be expressed on the cell surface, but it predominately localizes within sinusodial endothelia and its expression by lymphocytes has not been reported (35,36). Interestingly, antibody blockage of HA binding to HA receptor for endocytosis impairs tumor cell metastasis, a process likened to active lymphocyte extravasation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The short half-life of HMW-HA conjugates 57,65,66 is most likely due to HA clearance from the blood by the HARE receptor present in the liver and spleen. 5 Improvement in the distribution of HA conjugated drugs in vivo may be achieved by reducing endogenous HA blood clearance mechanisms. Luo et al suggested that systemic HA clearance can be reduced by pre-treatment with a high molecular weight saccharide that competes with HA for binding during clearance but not during target cell drug internalization.…”
Section: B Hyaluronan Conjugates As Drug Carriersmentioning
confidence: 99%
“…3 HA turnover is due to local cellular catabolism, removal by an HA endocytosing receptor (LYVE-1) on cells located in the lymphatics, 4 and systemic clearance from the blood by the HARE receptor on liver sinusoidal endothelial cells. 5 In skin, HA has a half-life of over a day. 6 In contrast, circulating high molecular weight HA (HMW-HA) has a half-life of two to five minutes.…”
mentioning
confidence: 99%
“…It is expressed at high levels in the sinusoidal endothelial cells of the spleen, lymph nodes, and liver. 18,21 In this study, we present evidence that stabilin-2 is also expressed in human monocyte-derived macrophages (HMDMs). These findings compelled us to speculate that stabilin-2 may participate in the recognition and engulfment of apoptotic and aged cells in macrophages.…”
mentioning
confidence: 94%
“…16 Stabilin-2 is a large multifunctional receptor, which harbors seven FAS1 domains, four EGF-like repeats, and a link domain. Stabilin-2 was initially identified as the endocytic hyaluronan receptor on rat liver sinusoidal endothelial cells 17,18 and has also been reported to function as a scavenger receptor, which effects the endocytosis of modified LDL and glycation end products. 19,20 Stabilin-2 also has been shown to bind to Gram-negative and Gram-positive bacteria, thereby suggesting the potential involvement of stabilin-2 in the immune response.…”
mentioning
confidence: 99%